Anti-feedant and Molluscicidal activities of selected spices against achatina fulica (Gastropoda Achatinidae) - Dzulsuhaimi Daud (Tanjong Malim, 2023)
Anti-feedant and Molluscicidal activities of selected spices against achatina fulica (Gastropoda Achatinidae) by Dzulsuhaimi Daud